2004
DOI: 10.1027/1015-5759.20.3.149
|View full text |Cite
|
Sign up to set email alerts
|

A Triadic Approach to the Construct Validity of the Assessment Center

Abstract: This study examined the influence on construct validity of implementing the triad Feeling, Thinking, and Power as a taxonomy for behavioral dimensions in assessment center (AC) exercises. A sample of 1567 job applicants participated in an AC specifically developed according to this taxonomy. Each exercise tapped three dimensions, one dimension from each cluster of the taxonomy. Confirmatory Factor Analysis of the multitraitmultimethod matrix showed evidence for construct validity. Thus, the ratings matched the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Based on a job analysis conducted for an earlier study, three dimensions were chosen to be assessed in the AC and the interview: Systematic Planning (prioritizing tasks, making plans for tasks and projects, making appointments in due time, and allocating tasks), Leadership Behavior (striving for and assuming responsibility for tasks and groups, coordination of teams, and arguing for one's point of view in groups), and Cooperation (assisting others with problems they may have, considering the needs of others, being prepared to compromise with others, and mediating between diverging points of view). These three dimensions correspond to the thinking–power–feeling taxonomy suggested for ACs (Kolk, Born, & van der Flier, 2004). As in many ACs (cf.…”
Section: Methodsmentioning
confidence: 97%
“…Based on a job analysis conducted for an earlier study, three dimensions were chosen to be assessed in the AC and the interview: Systematic Planning (prioritizing tasks, making plans for tasks and projects, making appointments in due time, and allocating tasks), Leadership Behavior (striving for and assuming responsibility for tasks and groups, coordination of teams, and arguing for one's point of view in groups), and Cooperation (assisting others with problems they may have, considering the needs of others, being prepared to compromise with others, and mediating between diverging points of view). These three dimensions correspond to the thinking–power–feeling taxonomy suggested for ACs (Kolk, Born, & van der Flier, 2004). As in many ACs (cf.…”
Section: Methodsmentioning
confidence: 97%
“…Several studies have already demonstrated increases in the construct validity of ACs by improving the observation of the behaviors shown during the exercise. This was accomplished either by reducing the number of dimensions to rate (Kolk, Born, & Van der Flier, 2004), by ensuring that the behaviors to be rated will be visible in the exercise (Klehe et al, 2008;Lievens, Chasteen, Day, & Christianson, 2006), by frame-of-reference trainings (Woehr & Huffcutt, 1994), and by using behavioral checklists instead of overall trait ratings (Jackson, Barney, Stillman, & Kirkley, 2007). Although the effects on construct validity tend to be small, these findings suggest that more systematic procedures that enable AC developers to select independent and easily measurable (behavioral) dimensions will help distinguish between these dimensions.…”
Section: Construct Validitymentioning
confidence: 99%
“…In agreement with Kolk et al (2004) it is worthwhile to note that AC dimensions are never completely orthogonal and therefore less discriminant validity may naturally be expected. In the ALS simulation for example it is expected that similar behaviour would relate to the winning business and business acumen competency dimensions.…”
Section: Discussionmentioning
confidence: 57%
“…The results of the study hold implications for improving construct validity of the LADC through improved AC design. Construct validity of ACs depends primarily on the accuracy of ratings and thus assessors' ability to process complex cognitive information inherent to the AC process (Kolk et al, 2004;Melchers et al, 2010;Moses, 2008;Thornton and Krause, 2009). In the LADC the assessors' cognitive load was affected by the large number of competency dimensions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation